Optimizing 18F-FDG Uptake Time Before Imaging Improves the Accuracy of PET/CT in Liver Lesions. - Al-Faham, Zaid; Jolepalem, Prashant; Rydberg, John; Wong, Ching-Yee O. (Journal of Nuclear Medicine Technology, 2016)
Unlabelled: (18)F-FDG PET/CT has emerged as one of the fastest-growing imaging modalities. A shorter protocol results in a lower target-to-background ratio, which can increase the challenge of identifying mildly (18)F-FDG-avid lesions and differentiating inflammatory or physiologic activity from malignant activity. The purpose of this study was to determine the delay between radiotracer injection and imaging that optimizes target-to-background ratio while maintaining counts high enough to ensure scan sensitivity.Methods: The study included 140 patients (66 male and 74 female; age range, 42-95 y) with suspected hepatic lesions as seen on an (18)F-FDG PET scan. SUV was determined as region-of-interest activity/(dose/total body weight).Results: The mean injected dose was 610 ± 66.6 MBq (16.5 ±1.8 mCi), with a mean glucose level of 107 ± 26.6 mg/dL (standardized to 90 mg/dL). The uptake time before imaging ranged from 61 to 158 min, with a mean of 108.8 ± 24.8 min. The P values for the correlation of SUV to time were 0.004, 0.003, and 0.0001 for malignant lesions, benign lesions, and background hepatic tissue, respectively.Conclusion: An approximately 90-min time window from (18)F-FDG injection to PET imaging would significantly improve target-to-background ratio and, thus, quantitation and visual interpretation. This benefit outweighs the minimal loss in patient throughput.